Боротьба міліції з проституцією в УСРР у добу непу (1921–1929 рр.) - Греченко, В. А.; Grechenko, V. A.; ORCID: http://orcid.org/0000-0002-6046-0178 (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 1 (68). - С. 22-33., 2015)
Розглянуто основні аспекти боротьби міліції з проституцією в період нової економічної політики в Україні, причини проституції, її рівень.

With coming to power of bolshevists there is a prostitution, criminality and another negative social phenomena began to be examined as disgraceful heritage, vestige of capitalist line-up. This idea underlay activity of the soviet state on a fight against a prostitution. During active legislative activity norms were accepted about the criminal proceeding of persons, engaging women in the sphere of commercial sex and containing the dens of debauch. The legislative fixing of possibility of a force physical examination of persons probably having a venereal disease had influence on the decline of height of number of infected. Measures accepted in the Soviet state, on a fight against a prostitution were more effective, than those, that were used in preceding periods. However the self phenomenon continued to exist, «sale love» continued to be in demand, though substantially less, than before. Insufficient efficiency of the conducted events was partly conditioned by absence of the required capital investments, that explained by limit possibilities of country trying to overcome an economic crisis, and also walking of the state away from a market economy and passing to industrialization that entailed application of new measures in regard to the sphere of commercial sex.

Рассмотрены основные аспекты борьбы милиции с проституцией в период новой экономической политики в Украине, причины проституции, ее уровень.
Grechenko, V.A. (2015), “Fight of militia against a prostitution in Ukrainian SSR during a new economic policy (1921–1929)” [“Borotba militsii z prostytutsiieiu v USRR u dobu nepu (1921–1929 rr.)”], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 1, pp. 22-33.
Греченко, В. А. Боротьба міліції з проституцією в УСРР у добу непу (1921–1929 рр.) // Вісник Харківського національного університету внутрішніх справ. - 2015. - № 1 (68). - С. 22-33.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; міліція; militia; милиция; проституція; нова економічна політика; злочинність; історія; Україна. Ukraine. Украина; prostitution; new economic policy; criminality; проституция; новая экономическая политика; преступность; история; New Economic Policy